Porcine reproductive and respiratory syndrome virus transmission among smallholder pig farms in Western Uganda - Niwandinda, E.; Hasahya, Emmanuel; Bugenyi, A.W.; Bogere, P.; Byaruhanga, J.; Alarcón, P.; Kirunda, H.; Heo, J.; Masembe, C. (Elsevier, 2025)
Pig production is a rapidly growing sector in Uganda, especially among smallholder farmers to whom it provides a vital source of income. However, the burden of productivity-limiting diseases such as Porcine Reproductive and Respiratory Syndrome (PRRS) poses a significant challenge. This is exacerbated by the paucity of information on the occurrence of these pathogens within the country, highlighting the need to study their transmission dynamics for effective control. Here, we modelled the transmission of PRRS in western Uganda and evaluated its control under strategies targeting closure of biosecurity gaps related to practices such as equipment sharing, free ranging, boar sharing, farm visits, and restocking. We used data from 398 pig-farming households to assess husbandry practices, and to estimate contact rates and distances for simulating the spread of PRRS among the 44,125 farms in the study area. Biosecurity measures were found to be low among pig farms in the region, with only 0.8% of them keeping their entire herd confined all-year round, limiting access to unauthorized persons, and using disinfectants. Under the current state of biosecurity, a PRRS outbreak would result in 17. 57% of the pig farms in the region being infected within two years, with the medium and large-scale smallholder farms being most affected. The outbreak would persist beyond 2 years (with a 67.80% likelihood), stabilizing around 700 days post-introduction; reaching a prevalence of 5.15%; and with a median of 17 farms being infected daily during this endemic phase. However, eliminating visitor traffic could entirely halt PRRS spread, while eliminating risks associated with boar sharing, restocking, and scavenging would lead to reductions of 99.85%, 99.44%, and 40.67%, respectively. Furthermore, even a moderate adoption of improved biosecurity measures related to farm visits or boar sharing, could significantly reduce the effects of PRRS in the region. For instance, reducing the frequency of farm visits or boar sharing by 25% across all pig farms could reduce PRRS transmission by 99.61% or 73.95% respectively. This outcome could also be achieved through a targeted adoption rate of 50% within large-scale smallholder farms coupled with a 25% rate for medium-scaled ones. Our results highlight the necessity of promoting enhanced on-farm biosecurity practices in smallholder pig farms, given the challenges posed by productivity-limiting diseases such as PRRS, in Uganda’s rapidly growing piggery industry.